Incentivizing efficient utilization without reducing access: The case against cost-sharing in insurance - Markus Peter Fels (Karlsruher Institut für Technologie (KIT), Institut für Volkswirtschaftslehre (ECON), 2017)
Cost-sharing is regarded as an important tool to reduce moral hazard in health insurance. Contrary to standard prediction, however, such requirements are found to decrease utilization both of efficient and of inefficient care. I employ a simple model that incorporates two possible explanations - consumer mistakes and limited access - to assess the welfare implications of different insurance designs. I find cost-sharing never to be an optimal solution as it produces two novel inefficiencies by limiting access. An alternative design, relying on bonuses, has no such side effects and achieves the same incentivization.
urn:nbn:de:swb:90-755130
Keywords: D82; I13; I14; 330; Moral Hazard; Limited Access; Cost-Sharing; Insurance Rebates